Condition monitoring on hydraulic pumps – lessons learnt - Paulmann, G.; Mkadara, G. (My University, 2017)
An overview to the performed analysis and lessons-learnt approach from flight control & hydraulic designers perspective on a condition monitoring (CM) concept for hydraulic pump application for helicopters is given.